VIS-NIR-SWIR spectroscopic mapping for classification of hydrothermal-metasomatic alterations on the flanks of the Stolbovoe uranium deposit (Eastern Cis-Sayan) - E. N. Karmanov; N. V. Ledeneva; V. A. Rassulov; A. V. Tomashev (Известия высших учебных заведений: Геология и разведка, 2022)
Background. The Stolbovoe deposit is located in the northern part of the Eastern Sayan, in the Nizhneudinsky district of the Irkutsk region, within the N-47-IX map sheet. The surveying of the territory began in the sixties of the last century. The Stolbovoe deposit was discovered based on direct search signs (radioactivity). At the same time, the search was not aimed at revealing new deposits hidden under the Riphean cover; therefore, most of the territory remained unexplored.Aim. To map and classify the near-ore hydrothermal-metasomatic alterations manifested on the flanks of the Stolbovoe uranium deposit.Materials and methods. During the 2018–2020 period, within the framework of prospecting work, the employees of the All-Russian Scientific-Research Institute of Mineral Resources named after N.M. Fedorovsky (VIMS) carried out the mapping of ore alterations using an innovative method of Infrared (IR) spectroscopy. The diagnostics of mineralization was carried out using a portable TerraSpec 4 Hi-Res spectrometer. The instrument was used to measure diffuse reflectance spectra in the Ultraviolet-Visible-Short-Wave Infrared (UV-Vis-SWIR) ranges; the composition of various mineral phases was determined using the TSGVersion 7 database and software.Results. This study confirmed the efficiency of the method applied for the diagnostics of all varieties of clayey (kaolinite, montmorillonite) and fine micaceous (phengite, sericite, paragonite and their illite varieties) minerals, as well as carbonates (dolomite, ankerite, siderite) and chlorites in the rock in situ or in samples without preliminary sample preparation.Conclusions. The use of the described method for investigating cores and samples of the Stolbovoe uranium deposit (East Sayan region) made it possible to classify the epigenetic changes in rocks and to map hydrothermal-metasomatic halos, including those near-ore, formed by mineralization that could not be identified by conventional visual and optical methods.